EXPERT OPINION AND PRODUCT QUALITY: EVIDENCE FROM NEW YORK CITY RESTAURANTS. (30th December 2014) - Gergaud, Olivier; Storchmann, Karl; Verardi, Vincenzo
<x xml:space="preserve">Abstract</x> We analyze whether consumers' quality perception and/or producer investment of New York City restaurants, measured by Zagat scores, responds to newly appearing expert opinion, measured by Michelin scores. Answering this question is of general economic interest as it applies to all markets with information asymmetries. Employing a difference‐in‐differences approach as well as a propensity score matching approach we find significant Michelin treatment effects on food and décor quality. Based on these changes, we find a Michelin‐induced price increase of approximately 30% per Michelin star. To examine whether the improved food and nonfood quality is based on restaurant investments or is merely imagined, we analyze nonfood investments by referring to Wine Spectator wine list awards. Our analysis suggests that Michelin‐reviewed restaurants are significantly more likely to invest in their wine list than others. As a result, Michelin reviewed restaurants are more likely to improve food and nonfood (esp. décor) quality leading to significant price increases. However, while restaurants that increase prices only due to décor and service improvements are more likely to go out of business, food improvements appear to secure a restaurant's survival. (JEL D11, L15, L66)